Assessment and visualization of inherent vulnerability of urban population in India to natural disasters. (2nd July 2020) - Anees, M. M.; Shukla, Roopam; Punia, Milap; Joshi, P. K.
ABSTRACT: Growth of Indian urban population is bound to have a substantial influence on the economic and environmental stability of India. India has the potential of adding double the current urban population, and with intensifying climate change-related disasters it can be home to millions of vulnerable habitants. This study captures the inherent characteristics of the urban population at the district level to compute the inherent vulnerability (IV) index. Our aim was to identify vulnerable regions of the urban population and prepare a composite ranking. Districts were grouped into urban population classes (UPC) for better comparability. We analysed data on 28 indicators under five major components namely, infrastructural, technological, social, financial and ecological. Our results show that 45% and 42% of districts fall under medium and high vulnerability category, respectively. Majority of the high vulnerable districts are clustered in the states already reported for lower Human Development Index (HDI) and high poverty levels in the past. In all the UPCs, the ecological component was observed to be the weak link. In addition, the technology component revealed a major gap. Findings of the study could assist policy makers in identifying the determining components of IV which can be focused for resource and manpower investment.